Prevention and control strategies for children Kashin–Beck disease in China: A systematic review and meta-analysis. Issue 36 (September 2019) - Yu, Fang-fang; Qi, Xin; Shang, Yan-na; Ping, Zhi-guang; Guo, Xiong
Abstract: Background: To evaluate prevention and control strategies for children with Kashin–Beck disease (KBD) in China through a systematic review and meta-analysis. Methods: We conducted literature searches of articles indexed in Web of Knowledge, PubMed, Springerlink, Elsevier, the Chinese National Knowledge Infrastructure, and Wanfang data until February 2019. Search terms included "Kashin–Beck disease" or "KBD, " and "improvement of water" or "change of grain" or "salt-rich selenium" or "comprehensive measures." Eligible studies were prospective trials of interventions in endemic area. Data extraction was performed by 2 independent authors using predefined data fields that also included quality evaluation. Results: We screened 1183 potentially relevant articles, and included 22 studies that reported 24 trials, with data from 3700 healthy children and 2961 children KBD. The pooled odds ratios (ORs) and confidence intervals (95% CIs) for primary prevention new incidence in healthy children following interventions to comprehensive measures, change of grain, salt-rich selenium, and improvements of water were 0.15 (0.02, 0.95), 0.15 (0.03, 0.70), 0.19 (0.09, 0.38), and 0.20 (0.09, 0.42), respectively. The OR (95% CI) for clinical improvement in children KBD following interventions to improvement of water, salt-rich selenium, comprehensive measures, and change of grain were 5.03 (3.21, 7.89), 4.39 (3.15, 6.11), 2.98 (1.61, 5.52), and 2.35 (1.59, 3.47), respectively. All interventions showed significant differences and were effective ( P  < .05). Conclusion: Comprehensive measures and change of grain were the most effective measures in preventing new case, whereas improvement of water and salt-rich selenium resulted in clinical improvements in children KBD. Abstract : Supplemental Digital Content is available in the text